2021
DOI: 10.1038/s41598-021-87866-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diagnostic value of 68 Ga-DOTATOC PET/MRI and standalone MRI for the detection of intracranial meningiomas

Abstract: To evaluate the diagnostic performance of magnetic resonance imaging (MRI) alone in comparison to positron emission tomography/ magnetic resonance imaging (PET/MRI) in patients with meningiomas. 57 patients with a total of 112 meningiomas of the brain were included. PET/MRI, including a fully diagnostic contrast enhanced MRI and PET, were acquired. PET/MRI was used as reference standard. The size and location of meningiomas was recorded. Likelihood-ratio chi-square tests were used to calculate p-values within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The initial search yielded 1606 published articles (PubMed: 803; Scopus: 673; Web of Science: 107; Cochrane: 23). A total of 63 studies were included with the a priori criteria: 25 were case reports and 38 were case series, categorized with levels of evidence IV and V, respectively [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search yielded 1606 published articles (PubMed: 803; Scopus: 673; Web of Science: 107; Cochrane: 23). A total of 63 studies were included with the a priori criteria: 25 were case reports and 38 were case series, categorized with levels of evidence IV and V, respectively [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
“…DOTATATE (54.5%) was utilized more frequently than DOTATOC (45.5%). In meningiomas, [ 68 Ga]Ga-DOTA-SSTR PET studies were implemented to: (1) evaluate intraosseous or infracranial extension [ 15 , 31 , 79 ]; (2) detect lesions difficult-to-identify on MRI [ 30 , 63 ]; (3) differentiate residual/recurrent tumor tissue versus non-tumor tissue [ 14 ], such as surgical scarring [ 38 ] or post-therapy changes [ 53 ]; (4) confirm the diagnosis of meningiomas (high tracer uptake) [ 35 , 71 , 72 ] and differentiate those from other pathologies with lower tracer uptakes, both tumoral [ 44 , 54 , 55 , 58 ] and non-tumoral [ 40 , 42 ]; (5) stage recurrent or systemic disease [ 34 , 50 , 56 ]; (6) quantify tracer uptake (SSTR2 expression) [ 61 , 62 , 77 ] and match/mismatch with FDG uptake (metabolic rate) [ 35 , 52 ]; (7) evaluate postoperative extent of resection [ 60 , 65 ]; (8) predict tumor growth [ 45 ]; and appraise the diagnostic accuracy of hybrid PET/MRI scans [ 13 , 37 , 63 ]. In pituitary adenomas, [ 68 Ga]Ga-DOTA-SSTR PET studies were utilized to confirm biologically active post-surgical residual tumor tissue in concomitance with FDG PET/CT studies [ 16 ], or for differential diagnosis with synchronous meningiomas [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published paper, Einhellig et al [ 35 ] performed a prospective head-to-head comparison between 68 Ga-DOTATOC PET/MRI versus standalone MRI in 57 patients harboring 112 meningiomas. Histology, as a reference standard, was available in 32 cases, while for the remaining 25, final diagnosis was made on the basis of clinical and imaging correlation.…”
Section: Resultsmentioning
confidence: 99%
“…Rachinger and colleagues demonstrated that standard MRI has sensitivity of 79% and specificity of 65% in distinguishing meningioma from tumor-free tissues 17 . Another group showed that MRI alone can achieve sensitivity of 95% and specificity 88% in the diagnosis of meningioma in a cohort of 57 patients, but noted that diagnostic accuracy diminishes in cases of small lesions (< 0.5 cm 3 ) and certain difficult locations such as skull base 6 . For transosseous growing meningiomas, MRI’s sensitivity was even lower at 54% 5 .…”
Section: Discussionmentioning
confidence: 99%